The Understanding of Al-Adabiy Al-Ijtima’iy (A Study of the Verses of Happiness in The Book of Tafsir Al-Azhar Buya Hamka) - Nur, Afrizal; Yuzar, Sri Kurniati; bin Mohd Sa’ad, Mohd Fa’izul Amri (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The elaboration of the meaning and interpretation of each verse of the Qur'an continues to this day. This fact emphasizes his miracles that will never be matched by anyone. This article is an innovation of the Tafsir methodology, in this case it focuses on the orientation and style of interpretation of the Qur'an in the 20th century AD, the study of the verses of Happiness in the Book of Tafsir Al Azhar Buya. This book of Tafsir is more dominated by the al-adabiy wal Ijtima'iy style, which is a style that takes pictures of various events, social phenomena and the community. In the perspective of the methodology, the approach used is normative-historical by revealing the interpretation of the text and socio-culture of the community to the first and present recipients. This research is a qualitative research with a literature review model (library research). Among his findings are stories about the struggle of the Acehnese people against the Dutch colonialists and their